Pengembangan Backend Investasi Berbasis Website pada Ekosistem Digital Ihya dengan Metode Iterative Incremental - Krisna Dwi Permana; Rahmat Fauzi; Sinung Suakanto (STMIK Budi Darma, 2022)
Technological developments in the industrial era 4.0 are very fast coupled with the COVID-19 pandemic. The digital ecosystem is one that has developed rapidly during the pandemic, many people need a complete platform to meet all their needs, so the presence of a digital ecosystem is expected to provide all user needs. One of the things that users want in a digital ecosystem is an investment module. The existence of a digital ecosystem with an investment module will greatly help people who need capital and creation due to the pandemic. However, at this time there are still few digital ecosystems that have this module. So there is a need for a digital ecosystem that has an investment module to make it easier for users to access and use it, so the creation of a website-based digital ecosystem called Ihya, especially on the investment module. The creation of the digital ecosystem website was made using the iterative incremental method as its development method. The development of the Ihya digital ecosystem on investment modules made using the PHP programming language with the Laravel framework and the CSS Bootstrap framework, and stored in a MySQL database. The investment module in the Ihya digital ecosystem was tested using the black-box testing, user acceptance test, and load test methods. After testing, the Ihya digital ecosystem investment website meets user needs as an investment platform with a user acceptance test value of 85.1%.